2008
DOI: 10.3892/or.19.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin as a marker for determination of tissue viability after radiofrequency ablation in a murine liver tumor model

Abstract: In this proof-of-principle study, the necrosis avid agent hypericin was investigated as a potential indicator for early therapeutic response following radiofrequency ablation (RFA) of murine liver tumors. Eight mice bearing intrahepatic RIF-1 tumors were intravenously injected with hypericin 1 h before or 24 h after RFA treatment. Mice were euthanized 24 h after hypericin injection and excised livers were investigated by means of fluoromacroscopic and fluoromicroscopic examinations in combination with conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…Although not evaluated in this work, 64 Cu-bis-DOTA-hypericin may also be an efficient photodynamic agent and thus may be suitable for both diagnostic and therapeutic applications. Van de Putte et al (21,28) investigated the distribution of hypericin in a murine liver tumor model and found that hypericin was a necrosis-avid agent. They showed that hypericin specifically stained necrotic tissue by interacting with necrotic cellular debris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not evaluated in this work, 64 Cu-bis-DOTA-hypericin may also be an efficient photodynamic agent and thus may be suitable for both diagnostic and therapeutic applications. Van de Putte et al (21,28) investigated the distribution of hypericin in a murine liver tumor model and found that hypericin was a necrosis-avid agent. They showed that hypericin specifically stained necrotic tissue by interacting with necrotic cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“…Because the compound showed a peculiar affinity for irreversibly damaged ischemic or necrotic tissues, hypericin has also been recognized as a nonporphyrin necrosis-avid agent (21). Radiolabeled derivatives of hypericin such as 123 I-iodohypericin have been studied in animal models of hepatic and myocardial infarction, though their mechanisms of action are still unclear (22,23).…”
mentioning
confidence: 99%
“…orthotopic Novikoff hepatoma [10] in Sprague-Dawley rats and ectopic R1 tumor [31][32][33][34] in WAG/ Rij rats, and ectopic RIF-1 in C3H/Km mice [35][36][37]. Relative to subcutaneous allografts of these tumor cell lines, liver implantation of tissue fragment has further upgraded their research utilities and clinical relevance [31][32][33][34][35][36][37].…”
Section: Implanted Rodent Liver Tumor Modelsmentioning
confidence: 99%
“…This has led to a number of research extensions: i.e. from porphyrin to nonporphyrin-NACA species [18,19,72], from the usage for MRI [16][17][18][19][20] to SPECT [73] and OI [36,37], and from the primary application for determination of myocardial viability [20,[73][74][75] to anticancer therapeutic assessment [31]. One oncological potential is explained hereunder (Fig.…”
Section: Viability Determination After Tumor Ablation Using Necrosis mentioning
confidence: 99%
“…During a recent contrast agent study, Ni et al further expanded the role of Hyp in medicine by revealing that the necrosis avidity of Hyp is superior to its tumor affinity [6,[11][12][13] . Therefore, the necrosis avidity of radioiodinated Hyp, such as [ 123 I]iodohypericin ( 123 I-Hyp), has been used as a diagnostic tool for imaging ischemic myocardial infarction and therapeutic tumor www.nature.com/aps Li JJ et al Acta Pharmacologica Sinica npg necrosis [11][12][13][14][15][16][17] . Additionally, the potential use of 131 I-Hyp for the treatment of cancer has been investigated with encouraging results, which have been demonstrated in rodent tumor models [13,15] .…”
Section: Introductionmentioning
confidence: 99%